Competition and Irreversible Investments under Uncertainty - Michele Moretto (Fondazione Eni Enrico Mattei (FEEM), 2003)
This paper examines the effect of competition on the irreversible investment decisions under uncertainty as a generalization of the real option approach. We examine this issue with reference to an industry where each firm has only one investment opportunity which is completely irreversible and the product market reveals an inverted U-shape relationship between firm profits and industry size. That is, there are positive externalities for low level of the market size and negative externalities at high level of the market size. In the latter case, which corresponds to the traditional competitive industries, firms invest sequentially as market profitability develops. In the former case, which corresponds to industries in which investments are mutually beneficial, firms invest simultaneously after profitability of the market has developed sufficiently to capture all network benefits and to recover the option value of waiting. Put together, these extensions of the real option analysis, with strategic interactions, may help to explain both the cases of rapid and sudden developments such as the recent internet investments and the cases of prolonged start-up problems while waiting for the market to develop as the story of fax machines shows.
Keywords: D81; C73; G13; O31; 330; Competition; network effect; real options; Investitionsentscheidung; Wettbewerb; Netzwerkökonomik; Dynamisches Spiel; Theorie; Realoptionsansatz; Gleichgewichtsmodell